Conceptual apparatus formation of the problem of building of communicative reflection of future specialists - Svetlana V. Sannikova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is dedicated to the formation of the problem of building of communicative reflection of future specialists through the prism of historical aspect. The problem of reflection is one of the oldest and at the same time urgent problems that attracts attention of specialists from various fields of knowledge. This allowed us to study the experience of solving this problem, select the existing socio-historical background, to justify the timeliness and relevance of the research directions chosen by us. The category “reflection” considers to appear in Ancient times. The author relies on the works of Socrates, Plato, Aristotle and Plotinus. A brief description of reflection in the Middle Ages is based on the teachings of Augustine and Thomas Aquinas. The next historical period in the development of category “reflection” in our work is the philosophy of the New Age, based on the works of Lock, Leibnitz, Hegel. In the twentieth century they started studying reflection from the point of view of activity, the psychology of thinking, the laws of organization of communicative processes, as a means of arranging educational activities, the result of comprehension of one’s life. The paper deals with reflection in the aspect of communicative activity, an objective analysis of various approaches to the question of the essence of communicative reflection is carried out. The communicative aspect of reflection is represented by the works of S.L. Rubinstein, V.S. Bibler, M.M. Bakhtin, I.S. Kon et al. The author highlights the problem of the development of communicative reflection from the point of view of the second part of the twentieth century research. The definition of “specialist” is defined in the article by the discourse of the competence-based approach. The author focuses on the increased demand for a specialist, his ability to use communicative strategies and personal reflection in professional activities.